Superoxide Anion Production and Bioenergetic Profile in Young and Elderly Human Primary Myoblasts. (24th July 2018) - Marrone, Mariangela; La Rovere, Rita Maria Laura; Guarnieri, Simone; Di Filippo, Ester Sara; Monaco, Giovanni; Pietrangelo, Tiziana; Bultynck, Geert; Fulle, Stefania; Mancinelli, Rosa
Abstract : Sarcopenia is the age-related loss of skeletal muscle mass, strength, and function. It is associated with regenerative difficulties by satellite cells, adult muscle stem cells, and alteration of oxidative management, mainly the increase in superoxide anions (O2 − ). We aimed to investigate the relation between regenerative deficit in elderly and increase in O2 − production along with mitochondrial alterations. Myoblasts and myotubes from skeletal muscle of young and elderly healthy subjects (27.8 ± 6 and 72.4 ± 6.5 years old) were measured: (1) superoxide dismutase activity and protein content, (2) mitochondrial O2 − production levels, (3) O2 − production variability, and (4) mitochondrial bioenergetic profile. Compared to young myoblasts, elderly myoblasts displayed decreased SOD2 protein expression, elevated mitochondrial O2 − baseline levels, and decreased oxidative phosphorylation and glycolysis. Additionally, elderly versus young myotubes showed elevated mitochondrial O2 − levels when stressed with N-acetyl cysteine or high glucose and higher glycolysis despite showing comparable oxidative phosphorylation levels. Altogether, the elderly may have less metabolic plasticity due to the impaired mitochondrial function caused by O2 − . However, the increased energy demand related to the differentiation process appears to activate compensatory mechanisms for the partial mitochondrial dysfunction.